Associations between family characteristics and influenza vaccination coverage among children. (25th September 2019) - Ding, Xiaofei; Tian, Changwei; Wang, Hua; Wang, Wenming; Luo, Xiaoming
Abstract: Background: To assess the associations between family characteristics and influenza vaccination coverage among children. Methods: Data were used from the National Health Interview Survey 2011–2016. Results: The number of children ranged from 10 720 to 12 991 per year from 2011 to 2016. After adjustment for the high-risk status of influenza complications, sex, age, region, race and office visits of children, children of adults who received influenza vaccination were 3.83–4.79 times (the lowest and the highest odds ratios from 2011 to 2016) more likely to be immunized for influenza. Health insurance (1.36–1.61) was also associated with vaccination in children. However, the education level of family adults (0.59–0.79) and marital status of being widowed/divorced/separated (0.74–0.79) were negatively associated with vaccination uptake in children. The following characteristics were not major concerns with influenza vaccination in children: class of worker, years on the job, physical activity, drinking, smoking, hepatitis B immunization, number of family members aged ≥65 years and the ratio of family income to the poverty threshold. Overall, results from the pooled analysis (2011–2016) were consistent with the above-mentioned findings. Conclusions: Promoting parental influenza immunization and access to health insurance may be the most effective tools to promote the coverage of influenza vaccine among children.